The Effectiveness of Slow Deep Breathing as a Pain Management Intervention in Coronary Heart Disease: A Case Report - Yoyok Bekti PRASETYO; Tri Pemillu WATI (Namık Kemal Tıp Dergisi, 2025)
Patients with coronary heart disease often experience pain as their primary complaint. One effective nursing intervention to alleviate this pain is the practice of slow, deep breathing. This case study focuses on Mrs. A, a 57-year-old woman diagnosed with coronary heart disease five years ago. To help manage her pain, a slow, deep breathing relaxation technique was administered for four consecutive days. This nursing intervention not only reduced her pain but also calmed her down, highlighting its positive impact on pain management.